Burden of chronic obstructive pulmonary disease in Ghana and globally from 1990 to 2021, with projections through 2050: a systematic analysis based on the Global Burden of Disease Study 2021 - Mensah, Emmanuel; Liu, Min; Pan, Lingling; Lu, Wei; Zhou, Susheng; Zhang, Liqin; Cheng, Yusheng; Wei, Shuoshuo; Zha, Lei (Frontiers in Medicine, 2025)
ObjectiveTo assess the burden of chronic obstructive pulmonary disease (COPD) in Ghana within a global context, analyze temporal trends and risk factor attribution from 1990 to 2021, and project the future burden through 2050.Study designSecondary analysis of Global Burden of Disease (GBD) 2021 data, using statistical modeling to evaluate trends in COPD prevalence, incidence, mortality, disability-adjusted life years (DALYs), and attributable risk factors. Future projections were generated using Bayesian Age-Period-Cohort (BAPC) modeling.Data sourceGBD 2021 study, providing standardized estimates for 369 diseases across 204 countries and territories.Main outcome measuresCOPD-related deaths, prevalence, incidence, DALYs, age-standardized rates (ASRs), risk factor attribution, percentage change, age-specific death rates, and projections to 2050.ResultsFrom 1990 to 2021, Ghana experienced a 157% increase in COPD deaths (from 693 to 1,782), compared to a 49% global increase. Ghana's age-standardized death rate (ASDR) declined by only 7%, far below the global reduction of 37%. COPD prevalence in Ghana tripled, rising from 0.1 to 0.3 million, while incidence increased by 215% and DALYs by 171%. Globally, DALYs rose by 40% over the same period. In Ghana, household air pollution from solid fuel use accounted for 40% of COPD deaths, followed by ambient air pollution (25%). Globally, particulate matter pollution (41%) and smoking (36%) were dominant. Projections show continued increases in prevalence and incidence, particularly among adults aged 40–64, with plateauing DALYs and declining ASDR by the 2040s. Mortality increases sharply after age 60, with higher burden among males. Cohort analysis reveals rising mortality risk among those born after 1960.ConclusionDespite modest ASDR reductions, Ghana's absolute COPD burden is increasing, driven by preventable risk factors such as household air pollution. These findings highlight the need for targeted interventions, including clean cook-stove programs, improved air quality monitoring, and expanded access to spirometry and early screening. Such efforts are essential to reduce COPD-related morbidity and mortality and advance Sustainable Development Goal (SDG) 3.4.